If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8 = 16 + 10x Reorder the terms: -8 + 6x = 16 + 10x Solving -8 + 6x = 16 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -8 + 6x + -10x = 16 + 10x + -10x Combine like terms: 6x + -10x = -4x -8 + -4x = 16 + 10x + -10x Combine like terms: 10x + -10x = 0 -8 + -4x = 16 + 0 -8 + -4x = 16 Add '8' to each side of the equation. -8 + 8 + -4x = 16 + 8 Combine like terms: -8 + 8 = 0 0 + -4x = 16 + 8 -4x = 16 + 8 Combine like terms: 16 + 8 = 24 -4x = 24 Divide each side by '-4'. x = -6 Simplifying x = -6
| 0.3p/-p | | 3-2x+4x+6= | | 25A=5 | | 2x/x-3=9/x-7 | | 5c-4-3c+1=8c+2 | | 5x+3=6x+17 | | 48x+48=0 | | 3x-2=4(x+5) | | 6x+32=16x-8 | | 15y+5=5 | | 2x^2+19xy+24y^2=0 | | 16x^2-4x^4=0 | | 13x+32=16x-48 | | 15+x=1 | | 25x^2-1=10x | | BY=36 | | 7(x+7)=7x+49 | | 9x-(3/2)y=1 | | 1x+40=1x-10 | | (x^2+9)%(x-3) | | 12+3x^2+12x=0 | | b-c^2=5 | | 11x-13=8x+7 | | (4x^2-13x-5)%(x-2) | | h(x)=0.04x^2-3.5+100 | | 15a+5b=85 | | 4x+64x^2=0 | | 9b^2-Z=103 | | 7x^2-4x-2=0 | | -7(-1.75+-0.125y)-y=13 | | 4(3a+3)-(4a+6)=15 | | p=13-6 |